2000
DOI: 10.1038/sj.ejhg.5200393
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mutations in mismatch repair genes in Portuguese families with hereditary non-polyposis colorectal cancer (HNPCC) by a multi-method approach

Abstract: Mutation searching was performed in the hMSH2 and hMLH1 genes in 20 Portuguese families representing 124 registered affected individuals. Of the 20, 16 fulfilled the classic 'Amsterdam' criteria for HNPCC, whereas the remaining four families satisfied a modified set of criteria. These criteria required a CRC diagnosed before age 50 years and cancers diagnosed in two other relatives within the HNPCC spectrum. A multi-method approach was performed using the protein truncation test (PTT), single strand conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
0
16
0
2
Order By: Relevance
“…First, because the control population genotyped at the Mayo Clinic were not ethnically matched (nor ageand sex-matched) with the cases from the literature, there is the possibility of population stratification and bias. Similarly, the studies that we pooled for analysis were conducted with different populations (Sweden, 7 the United States, 13 Portugal, 17 Spain, 22 and Austria 26 ), which may have introduced a bias into our analysis. In addition, it is difficult to weld such different types of analyses into a single, coherent whole.…”
Section: In Silico Analysismentioning
confidence: 99%
“…First, because the control population genotyped at the Mayo Clinic were not ethnically matched (nor ageand sex-matched) with the cases from the literature, there is the possibility of population stratification and bias. Similarly, the studies that we pooled for analysis were conducted with different populations (Sweden, 7 the United States, 13 Portugal, 17 Spain, 22 and Austria 26 ), which may have introduced a bias into our analysis. In addition, it is difficult to weld such different types of analyses into a single, coherent whole.…”
Section: In Silico Analysismentioning
confidence: 99%
“…In spite of the large number of mutations previously described (The Human Gene Mutation Database, Cardiff http://archive.uwcm.ac.uk/uwcm/mg/hgmd/search.html) the present study reveals additional ones in Portuguese HNPCC families which, together with other published studies (Isidro et al, 2000;Fidalgo et al, 2000) indicate a relatively high number of novel mutations in the Portuguese population.…”
Section: Resultsmentioning
confidence: 47%
“…In many studies hMLH1 has been reported as the major gene. For example, in Portuguese and Brazilian populations mutations in hMLH1 were very frequent [22,23] and in a survey on Spanish families 64.3% of mutations were detected in hMLH1 and 35.7% in hMSH2 [24]. However, in some reports, such as a study by Irmejs et al [25] in Latvia, more mutations were reported in the hMSH2 gene.…”
Section: Discussionmentioning
confidence: 90%